(untitled) (Altre Modernità, 2022)
Marco Malvestio, The Conflict Revisited. The Second World War in Post-Postmodern Fiction (Oxford, Peter Lang, 2021, pp. 218 ISBN 978-1-78997-209-2) di Ilaria Stefani